Technological and psychological aspects of proctoring on-line tests from the participants’ perspective - Klement, Milan; Dragon, Tomáš; Bártek, Květoslav (International Journal of Innovative Research and Scientific Studies, 2025)
Privacy is often cited as a major issue in online testing using technological proctoring methods. In fact, this is perceived by test participants as the most significant aspect which has a major impact on the level of trust in the online testing environment. Even though the limitations related to the pandemic situation have already subsided, online testing has proven to be one of the ways to increase the efficiency of some important activities related to the agenda of higher education institutions. Although efficiency and flexibility of deployment is one of the undeniable advantages of online testing, it is necessary to emphasize that online testing using online proctoring systems raises some concerns among the participants, which may also have a negative impact on their results. For this reason, a research survey was conducted among the participants of the online admissions tests, in order to find out their readiness, but also the specific concerns and expectations that online proctoring brings from their perspective. Thus, although most respondents reported serious concerns about the use of online proctoring (e.g., concerns about privacy, psychological well-being, etc.), they did not fundamentally question the process per se and in many cases appreciated its benefits in enhancing protection against fraudulent behaviour.